العادة الدوطة في شبه القارة الهندية وحلولها على ضوء مقاصد الشريعة - Nurunnabi, Mohammad (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
The custom of dowry which has been widespread in the Indian sub-continent is one of the major reasons for domestic violence against women. Moreover, due to dowry system and gender-based inequality, this region kills thousands of women each year according to the international human rights organization. The anti-dowry law was added to the Indian criminal act in 1961, Bangladesh in 1980, and Pakistan in 1976. Nevertheless the dowry custom is still wide spreading extensively. This study aims to propose the solutions for dowry custom in Indian sub-continent based on maqasid al-shariah.